Experimental study on a floating scroll-type compressor driving a precooled JT cryocooler. (September 2020) - Shen, Yunwei; Liu, Dongli; Liu, Lei; Li, Sizhuo; Chen, Shuhang; Gan, Zhihua; Qiu, Min
Highlights: An oil-free floating scroll-type compressor is integrated with a JT cryocooler. Cool down and pressure regulation processes are presented. The cooling performance of the JT cryocooler is stable. The back pressure is proved to affect the exergetic efficiency. The exergetic efficiency can be increased by 13.67% by adjusting back pressure. Abstract: The performance of the compressor directly affects the energy and space usage of a Joule-Thomson cryocooler. Characterized by simplicity and high pressure ratio, a single-stage oil-free floating scroll-type compressor with a back pressure regulating valve is introduced to drive the precooled Joule-Thomson cryocooler to approach liquid helium temperature. Cool down and pressure regulation processes of this Joule-Thomson cryocooler are presented. The stable cooling capacity at liquid helium temperature is achieved by which the availability of this compressor is verified. By regulating the back pressure of the compressor, it is found that there exists an optimal back pressure with which the exergetic efficiency of the compressor can be maximized keeping a stable performance.